Analisis Hukum Islam terhadap Penggunaan IUD pada Pasangan Pernikahan Dini - Roby; Syarifuddin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the Islamic legal perspective on the use of Intrauterine Devices (IUDs) among underage married couples in Indonesia. The issue becomes increasingly relevant due to the continued occurrence of child marriage through marriage dispensation mechanisms, which often place adolescent wives at high risk of reproductive health complications, psychological instability, and socioeconomic vulnerability. This article aims to analyze the legal status of IUD use for underage couples from the perspective of Islamic law through the approach of Maqasid al-Sharia. The research employs normative legal research with a conceptual and statutory approach by examining Islamic legal sources, fiqh principles, and regulations related to marriage and reproductive health. The findings indicate that the use of IUDs for underage couples is legally permissible (mubah) and may become recommended (mandub) or even obligatory (wajib) in situations involving serious medical risks to the wife. This position is based on the principles of hifz al-nafs (protection of life) and hifz al-nasl (protection of progeny), as well as the fiqh maxim ad-dararu yuzal (harm must be eliminated). Furthermore, the use of IUDs is not considered contrary to Islamic teachings on procreation, but rather constitutes a preventive effort to ensure maternal health and family welfare. The study concludes that the use of IUDs among underage married couples reflects a contextual and humanitarian-oriented implementation of Islamic law aimed at achieving public benefit and preventing greater harm